Upaya World Food Programme (WFP) Dalam Menangani Ketidaktangguhan Pangan di Sierra Leone Tahun 2005-2013 - Perdana Yoga Yanugera, I Gede Made Ngurah; Fasisaka, Idin; Rainy Priadarsini, Ni Wayan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABST RACT   Sierra Leone has sufferred food crisis after the 12-year of civil war, which devastated all existing infrastructures in that country including their most prominent agriculture infrastructures. World Food Programme (WFP) has worked with Sierra Leone government since 1968 in handling their food insecurity problems. WFP programmes were launched in the form of nutritional aid to mothers and children, improving access to food, market, and social services. The aim of this research is to describe the WFP aids in handling the food insecurity problems in Sierra Leone which categorized as fragile state. This research will be studied with concepts of international organization, fragile state, food insecurity, and humanitarian aid, from 2005 until 2013. Keywords : World Food Programme, Sierra Leone, Food Insecurity, Humanitarian Aid